Architectural root responses of rice to reduced water availability can overcome phosphorus stress - Bauw, P. de; Vandamme, Elke; Lupembe, A.; Mwakasege, L.; Senthilkumar, Kalimuthu; Merckx, Roel (MDPI, 2019)
Drought and low phosphorus (P) availability are major limitations for rainfed rice production. Crop roots are important for soil resource acquisition and tolerance to P and water limitations. Two pot and two field trials were conducted to evaluate architectural root responses of contrasting rice varieties to combinations of different levels of P (deficient to non-limiting) and water availability (water stressed to submergence) and to identify the interactions with different varieties. Root development was then related to drought and/or low P tolerance. Although shoot and root growth responded more to P than to water availability, architectural root responses to water were much more prominent than responses to P availability. Reduced water availability decreased nodal thickness and increased secondary root branching, both factors partially enhancing P uptake efficiency and even overcoming a decreased root:shoot ratio under reduced water availability. In contrast to root thickness and secondary branching, basal lateral root density was strongly determined by variety and was related to enhanced P uptake. Reduced water availability induces root modifications whichapart from enhancing drought resiliencealso affect P uptake efficiency. Future research on rice roots and nutrient uptake may hence take into account the large effects of water on root development.